Hydrothermal variation in several deep caves of the Nullarbor Karst Plain, Australia - Lewis, Ian; Buzzacott, Peter (2013)
The Nullarbor karst plain in Australia contains many large caves along its southern coastal margin, 14 of which penetrate the regional groundwater basin near sea level to depths >10m. Since the mid-Miocene the Nullarbor has largely had an arid to semi-arid climate. Heat exchange between the atmosphere, the caves and their initial lake surfaces varies between caves.